Mix Method: Analysis of the Utilization of Recommendations from Accreditation Results in Improving the Quality of Higher Education - Candra, Hadi; Anwar, Khairul; Zebua, Ali Marzuki (Institut Agama Islam Negeri Lhokseumawe, 2024)
Accreditation is crucial for assessing higher education institution quality and holding institutions accountable to the community. However, accreditation recommendations are underutilized by the institutions. The issue may stem from educational institutions’ lack of knowledge regarding the utilization of assessment results or their failure to identify the necessity of employing such results. This research uses a mixed methods approach to analyze the utilization of accreditation recommendations at State Islamic Institute of Kerinci. This research encompasses both quantitative data collection (close-ended) and qualitative data collection (open-ended) for the purposes of integration. The research employs a data analysis technique that determines the percentage of questionnaire responses for quantitative results and analyzes qualitative data through reduction and presentation. Subsequently, both datasets were analyzed utilizing SWOT analysis. The success of accreditation recommendations at State Islamic Institute of Kerinci is evident from the 67% of respondents who support them. The analysis results demonstrate the institution's positive steps in incorporating accreditation recommendations to enhance higher education quality. This involves solid commitment from leadership and the academic community, enhancing academic career progression, and incorporating research results into teaching-learning process. However, challenges such as low trust, funding problems, and negative perceptions of programs and policies remain obstacles. Hence, recommendations were pinpointed to enhance future utilization of accreditation recommendations, focusing on internal communication, incentives, funding, program evaluation, collaboration, and overcoming challenges. These steps aim to assist State Islamic Institute of Kerinci better utilize accreditation recommendations, enhance institutional quality, and achieve higher education objectives.